Efferent compared to afferent neural substrates of the vergence eye movement system evoked via fMRI - Sangoi, Ayushi; Hajebrahimi, Farzin; Gohel, Suril; Scheiman, Mitchell; Alvarez, Tara L. (Frontiers in Neuroscience, 2025)
IntroductionThe vergence neural system was stimulated to dissect the afferent and efferent components of symmetrical vergence eye movement step responses. The hypothesis tested was whether the afferent regions of interest would differ from the efferent regions to serve as comparative data for future clinical patient population studies.MethodsThirty binocularly normal participants participated in an oculomotor symmetrical vergence step block task within a functional MRI experiment compared to a similar sensory task where the participants did not elicit vergence eye movements.ResultsFor the oculomotor vergence task, functional activation was observed within the parietal eye field, supplemental eye field, frontal eye field, and cerebellar vermis, and activation in these regions was significantly diminished during the sensory task. Differences between the afferent sensory and efferent oculomotor experiments were also observed within the visual cortex.DiscussionDifferences between the vergence oculomotor and sensory tasks provide a protocol to delineate the afferent and efferent portion of the vergence neural circuit. Implications with clinical populations and future therapeutic intervention studies are discussed.